HAJJ AND UMRAH AS A MEDIUM FOR MORAL EDUCATION IN ADDRESSING NARCISSISTIC TENDENCIES IN THE MODERN ERA - Hasanah, Uswatun; Khasanah, Uswatun; Syarif Zain, Zaki Faddad (Institut Agama Islam Negeri Metro, 2025)
In the modern era, the phenomenon of narcissistic tendencies has increasingly permeated the performance of Hajj and Umrah, obscuring the purpose of spirituality and replacing it with more secular motives. This raises concerns about the quality of moral education provided by the pilgrimage. The article aims to investigate the emerging phenomenon of narcissistic tendencies among Hajj and Umrah pilgrims, examining the underlying factors that drive such behavior and exploring effective strategies to address these challenges while preserving the spiritual essence of the pilgrimage. This study employed a qualitative research approach, utilizing in-depth interviews and direct participant observation to comprehensively explore the manifestations of narcissistic behaviors among Hajj and Umrah participants. Data analysis techniques using the Milles and Huberman models. The findings show that factors such as social pressure, the drive for social recognition, and the influence of social media play a significant role in encouraging narcissistic tendencies behavior among Hajj and Umrah pilgrims. However, it was also found that a holistic moral education approach by KBIHU Al-Multazam Waymili, including fostering spiritual values, providing moral material, personal counseling, strengthening habituation, being wise in using social media, and cultivating simplicity and self-reflection, can mitigate the negative impact of this phenomenon. In conclusion, the phenomenon of narcissistic tendencies in the Hajj and Umrah is a real challenge to maintain the values of spirituality and morality. However, this phenomenon can be overcome with the right moral education approach at the individual and community levels. Hajj and Umrah can remain strong mediums for moral education.